Interpreters with Lewis and Clark : the story of Sacagawea and Toussaint Charbonneau - Nelson, W. Dale (University of North Texas Press, 2003)
A frank portrayal of Toussaint Charbonneau, a French-Canadian fur trader, who, with his Shoshone Indian wife Sacagawea, joined the Lewis and Clark expedition in 1803. While Sacagawea assumed legendary status as a "token of peace", Toussaint has been maligned in fiction and nonfiction alike
Keywords: Sacagawea.; Sacagawea -- Family.; Charbonneau, Toussaint, -- approximately 1758-approximately 1839.; Charbonneau, Jean-Baptiste, -- 1805-1866.; Lewis and Clark Expedition -- (1804-1806); Charbonneau, Jean-Baptiste, -- 1805-1866; Charbonneau, Toussaint, -- approximately 1758-approximately 1839; Sacagawea; Charbonneau, Toussaint, -- ca. 1758-ca. 1839.; Shoshoni women -- West (U.S.) -- Biography.; Pioneers -- West (U.S.) -- Biography.; Indian interpreters -- West (U.S.) -- Biography.; West (U.S.) -- Discovery and exploration.; Frontier and pioneer life -- West (U.S.); TRAVEL -- General.; TRAVEL.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; Discoveries in geography; Families; Frontier and pioneer life; Indian interpreters; Pioneers; Shoshoni women; West United States; Lewis-and-Clark-Expedition; Ontdekkingsreizigers.; Indianen.; Ontdekkingsreizen.; États-Unis (Ouest) -- Découverte et exploration.; Translating and interpreting -- Biography.; Biographies; Biographies.